Heat gain in an internally dimpled tube heat exchanger - a numerical investigation. (2023) - Malapur, Harsh V.; Havaldar, Sanjay N.; Anderson, Gary A.
Abstract: Many researchers have looked at heat transfer improvement methods utilizing circular dimpled pipes, surfaces, and other methods in the past. The size and position of dimples, for example, have a major influence on the pipe's flow and thermal properties. Five internally dimpled pipe configurations were analyzed in this computational research. The flow was simulated using ANSYS Fluent 16, with water as the working fluid and steel pipes with internal dimples. The effect of dimple number and diameter on flow and thermal parameters was studied with the five different internal dimple configurations and compared them with plain tube heat exchanger thermal performance under similar conditions. Internal dimples (inside protrusions in tube heat exchanger) resulted in a larger pressure drop in the path of flow from entry to exit. It was discovered that dimples increased the pipe heat exchanger's heat transfer coefficient when compared to the plain tube heat exchanger. A higher pressure loss than plain pipe heat exchangers (HE) was found although the thermal performance was more than that for a plain pipe. The Reynolds number of flows was changed as a result of the pressure drop. When the Reynolds number was lower, the friction factor was found to be higher, resulting in increased heat exchange in the experiment. The results of the numerical analysis for the tube HE with dimples indicate that dimples help mixing of flow in the tube HE and a growth of thermal boundary layer which enhance heat between the hot fluid and cold fluid through the tube HE wall.